Effects of Abdominal Aortic Aneurysm Size on Mid- and Long-term Mortality After Endovascular Aneurysm Repair. (April 2019) - Jeon-Slaughter, Haekyung; Krishnamoorthi, Harish; Timaran, David; Wall, Amanda; Ramanan, Bala; Banerjee, Subhash; Timaran, Carlos H.; Modrall, J. Gregory; Tsai, Shirling
Purpose: To investigate the effect of abdominal aortic aneurysm (AAA) size on mid- and long-term survival after endovascular aneurysm repair (EVAR).Materials and Methods: Retrospective data were collected from 325 consecutive patients (mean age 69.7 ± 8.5 years; 323 men) who underwent EVAR for intact AAA at a single institution between January 2003 and December 2013. The primary endpoint was death at 3, 5, and 10 years after EVAR. Optimal cutoff points for AAA size and age were determined using receiver operating characteristics (ROC) curves. Time to event analyses (Kaplan-Meier curves and Cox proportional hazard models) were employed to determine any differences in all-cause mortality outcomes between AAA size groups. Cox models were adjusted for age and other comorbidities (hypertension, hyperlipidemia, coronary artery disease, smoking status, symptomatic status, and creatinine); the outcomes are reported as the hazard ratio (HR) with 95% confidence interval (CI).Results: The cohort was dichotomized according to the ROC analysis, which defined an optimal cutoff point of 5.6 cm for AAA size and >70 years for age. The mean follow-up period post EVAR was 45.5±29.2 months. In total, 134 (41.2%) patients died during the 10-year follow-up. Thirty-day mortality was 1.1% (2/184) in the patients with AAA <5.6 cm and 2.1% (3/141) in patients with AAA ≥5.6 cm (p=0.45). All-cause mortality was not significantly affected by comorbidities. However, AAA size ≥5.6 cm was associated with increased 3-year mortality risk (HR 1.59, 95% CI 1.001 to 2.52, p<0.049) but not 5-year (HR 1.44, 95% CI 0.98 to 2.10, p=0.062) or 10-year mortality (HR 1.28, 95% CI 0.91 to 1.80, p=0.149). After adjusting for comorbidities, AAA size ≥5.6 cm was no longer significantly associated with morality at any time point. Using a larger size cutoff (AAA size ≥6.0 cm) resulted in improved statistical significance in the unadjusted model. In the adjusted Cox model, AAA size ≥6.0 cm was significantly associated with increased risk of mortality at 3 years (HR 1.67, 95% CI 1.01 to 2.77, p<0.047), but not at longer time points.Conclusion: Our study demonstrates that midterm survival after EVAR is significantly and independently associated with AAA size even after correcting for comorbidities. However, in the long term, preoperative AAA size is not an independent predictor of mortality.